Ketidakpastian Ekspor Agrikultur Indonesia Pasca EUDR - Asyifa, Hanif Nindy (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This research investigates the influence of exchange rate, price volatility, industrial production index (IPI), and European Union Deforestation Regulation (EUDR) on agricultural exports from Indonesia to the European Union. Based on the secondary data from 2015 to 2024 and using panel regression, the results indicate that the exchange rate has no positive effect on agricultural exports while price volatility is significantly negative. Furthermore,py the higher the IPI in destination countries, the lower demand for Indonesian agricultural commodities. On the other hand, the application of EUDR contributes to exports through promoting supply chain transparency and sustainable practices when governments compete. These results suggest that complying with global environmental standards is a good strategy to maintain access to market and improve the country image of Indonesian agricultural products.